ESENSI PASTORAL SEKOLAH DALAM MEMBANGUN KOMUNITAS KRISTIANI DI SEKOLAH KATOLIK - Yohanes Chandra Kurnia Saputra (Bahasa Indonesia, 2023)
School pastoral is an activity that aims to develop, improve and foster the faithful life of Catholics in the school environment. So through the school pastoral, it is hoped that the Christian community in the school environment will really be realized. Christian community is a fellowship whose members believe in Jesus Christ and are able to realize the teachings of Jesus Christ in their lives. Writing this scientific article aims to answer several main questions related to the relationship between pastoral schools, Christian communities and Catholic schools, these questions include: What is the essence of school pastoralism in building Christian communities in Catholic schools? Is the pastoral essence of the school in line with the idea of ​​administering a Catholic school in accordance with the vision and mission of the Church? How is the division of tasks and responsibilities so that the pastoral school can run well? Based on the analysis and discussion, it can be concluded that school pastoral is an essential program that is really effective in efforts to build a Christian community in Catholic schools. In addition, looking at the pastoral goals of schools and the goals of Catholic schools, it can also be concluded that the pastoral essence of schools is also in line with the idea of ​​organizing Catholic schools in accordance with the vision and mission of the Church. In realizing a good and effective school pastoral, there needs to be cooperation between the school, parents of students and the Church. This concerns promotive tasks, facilitative tasks, and executive tasks.